90 NATURAL HISTORY OF MENOPAUSAL SYMPTOMS IN PRIMARY CARE PATIENTS. (1st March 2005) - Xu, J.; Neale, V.; Dailey, R.; Northrup, J.; Schwartz, K.
Abstract : Background: The association between changes in menopausal status and vasomotor, psychological and somatic symptoms reporting over the course of the menopause transition is not well understood. Objectives: 1) Determine the prevalence and the natural history of menopause symptoms among primary care patients approaching or at menopause; and 2) examine the relationships between self-reported symptoms, sociodemographic variables and menopausal status. Study Design: Cross-sectional self-report survey of 342 women aged 40 to 55 years (31.6% African American) were recruited from eight family practice centers in 2000-2001. Results: Among 251 women without surgical menopause, 133 (53.0%) were pre-menopausal; 72 (28.7%) were peri-menopausal and 46 (18.3%) were post-menopausal. Vasomotor symptoms were less common in pre-menopause compared to peri- and post- menopause (p<0.01), even though as many as 28.6% of the women with regular menstruation reported hot flashes and 18.8% had night sweats. Post-menopausal women reported more psychological symptoms, including loss of sexual interest, nervousness, and irritability (but not depression). Somatic symptoms, including memory loss, fast heartbeat, difficulty sleeping, and arm or leg numbness, were also associated with menopausal status. African-American women reported painful sex more often than whites (p<0.01). Education, practice location, and hormone therapy were not associated with any reported symptoms. Conclusions: Symptoms are not uncommon among pre-menopausal women and become more prevalent as the transition to menopause occurs. The prevalence of vasomotor symptoms in pre-menopausal women may be an under-recognized aspect of the natural history of the menopause transition.